2009
DOI: 10.1186/1756-0500-2-114
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationship analysis of cytotoxic cyanoguanidines: selection of CHS 828 as candidate drug

Abstract: BackgroundN-(6-(4-chlorophenoxy)hexyl)-N'-cyano-N''-4-pyridyl guanidine) (CHS 828) is the first candidate drug from a novel group of anti-tumour agents – the pyridyl cyanoguanidines, shown to be potent compounds interfering with cellular metabolism (inhibition of nicotinamide phosphoribosyl transferase) and NF-κB signalling. Substituted cyanoguanidines are also found in anti-hypertensive agents such as the potassium channel opener pinacidil (N-cyano-N'-(4-pyridyl)-N''-(1,2,2-trimethylpropyl)guanidine) and hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In particular hexyl, heptyl, and octyl are the best linkers while the shorter chain linkers give compounds that display a lower activity. Finally a bulky tail group that protrudes toward the solvent exposed surface is important for determining the potency, with a phenoxy group displaying the best potency . It is interesting that no X-rays or NMR conformational studies on 2 have been reported in order to unveil which conformer of cyanoguanidine prevails in solution and which is the preferred conformation at the binding site.…”
Section: Medicinal Chemistry Of Nampt Inhibitorsmentioning
confidence: 99%
“…In particular hexyl, heptyl, and octyl are the best linkers while the shorter chain linkers give compounds that display a lower activity. Finally a bulky tail group that protrudes toward the solvent exposed surface is important for determining the potency, with a phenoxy group displaying the best potency . It is interesting that no X-rays or NMR conformational studies on 2 have been reported in order to unveil which conformer of cyanoguanidine prevails in solution and which is the preferred conformation at the binding site.…”
Section: Medicinal Chemistry Of Nampt Inhibitorsmentioning
confidence: 99%